Dealer capacity and U.S. treasury market functionality - Darrell Duffie; Michael J. Fleming; Frank Keane; Claire Nelson; Or Shachar; Peter Van Tassel (Federal Reserve Bank of New York, 2023)
We show a significant loss in U.S. Treasury market functionality when intensive use of dealer balance sheets is needed to intermediate bond markets, as in March 2020. Although yield volatility explains most of the variation in Treasury market liquidity over time, when dealer balance sheet utilization reaches sufficiently high levels, liquidity is much worse than predicted by yield volatility alone. This is consistent with the existence of occasionally binding constraints on the intermediation capacity of bond markets.
Keywords: G01; G1; G12; G18; E58; 330; Treasury market; liquidity; volatility; dealer intermediation; value-at-risk